Targeting hypoxia-inducible factors for breast cancer therapy: A narrative review - Luo, Shuang; Jiang, Yu; Anfu Zheng,; Zhao, Yueshui; Wu, Xu; Li, Mingxing; Du, Fukuan; Chen, Yu; Deng, Shuai; Chen, Meijuan; Li, Wanping; Li, Xiaobing; et al. (Frontiers in Pharmacology, 2022)
A complex microenvironment between breast tumors and stromal cells promotes cancer progression. Hypoxia is one of the most common conditions in the tumor microenvironment that drives tumor development. Most hypoxia environment is induced by a family of transcription factors called hypoxia-inducible factors (HIFs), which induce the expression of various genes and interact with stromal cells to help cells adapt to hypoxia. The role of HIF-1 in breast cancer progression is well established, and HIF-1 have been considered as potential therapeutic targets for breast cancer. This mini-review discusses the role and mechanisms of HIF-1 in breast cancer progression, as well as ongoing therapeutic strategies targeting HIF-1. We mainly highlight targeting HIF-1 by conventional and newly discovered drug delivery systems（DDS） and drug therapies in breast cancer microenvironment.